(untitled) (Global Journal of Medical Research, 2015)
Introduction-Prion diseases are neurodegenerative diseases that have incubation period. Five prion diseases are recognized they are kuru, Creutzfeldt-Jakob disease (CJD), variant CJD, Gerstmann-straussler Scheinker syndrome (GSS) and fatal familial insomnia1. Among all these disease, CJD accounts for 90% of all prion disease. One case of CJD occurs among 1,000,000 populations per year. It is such a rare presentation. Dementia and myoclonus are the most common presenting condition of CJD. This is a rare case report of a patient who had a rare clinical presentation, and finally it was diagnosed to be a case of CJD.